2015
DOI: 10.1371/journal.pone.0144824
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of β-Blockers, Angiotensin II Receptor Blockers, and a Novel AT2R Agonist NP-6A4 on Stress Response of Nutrient-Starved Cardiovascular Cells

Abstract: In order to determine differences in cardiovascular cell response during nutrient stress to different cardiovascular protective drugs, we investigated cell responses of serum starved mouse cardiomyocyte HL-1 cells and primary cultures of human coronary artery vascular smooth muscles (hCAVSMCs) to treatment with β-blockers (atenolol, metoprolol, carvedilol, nebivolol, 3μM each), AT1R blocker losartan (1μM) and AT2R agonists (CGP42112A and novel agonist NP-6A4, 300nM each). Treatment with nebivolol, carvedilol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…The X-linked Agtr2 that codes for AT2R is a 30-year old mechanistic target for treatment of CVD 32 37 . AT2R activation improves survival of mouse HL-1 cardiomyocytes and human coronary artery vascular smooth muscle cells under conditions of serum starvation 65 and reduces infarct size after myocardial infarction in murine models 35 , 66 . Increased Agtr2 expression in the female vasculature is implicated in the increased female-specific protection from hypertension, vascular injury, and renal function 32 34 .…”
Section: Discussionmentioning
confidence: 98%
“…The X-linked Agtr2 that codes for AT2R is a 30-year old mechanistic target for treatment of CVD 32 37 . AT2R activation improves survival of mouse HL-1 cardiomyocytes and human coronary artery vascular smooth muscle cells under conditions of serum starvation 65 and reduces infarct size after myocardial infarction in murine models 35 , 66 . Increased Agtr2 expression in the female vasculature is implicated in the increased female-specific protection from hypertension, vascular injury, and renal function 32 34 .…”
Section: Discussionmentioning
confidence: 98%
“…However, AT 2 R stimulation also usually involves an anti-inflammatory effect that may contribute to the beneficial AT 2 R-mediated anti-fibrotic effects. Most data related to chronic AT 2 R stimulation have been obtained using C21, although there are a number of other AT 2 R agonists beginning to emerge in the literature ( Jones et al, 2011 ; Guimond et al, 2014 ; Del Borgo et al, 2015 ; Mahmood and Pulakat, 2015 ) that require rigourous in vivo testing in a similar manner to C21. Such studies will shed further light on the clinical potential of AT 2 R agonists in CVD.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported recently that a novel peptide agonist for the angiotensin II type 2 receptor AT2R named NP-6A4 is effective in improving cardiomyocyte and vascular smooth muscle survival under nutrient deficiency stress [64]. We also showed that NP-6A4 could increase MCL-1 expression in cardiovascular cells [64]. We propose that a synergistic treatment with Rapamycin and NP-6A4 would be beneficial in mitigating some of the negative effects of Rapamycin treatment and enhancing cardioprotection in diabetes.…”
Section: Discussionmentioning
confidence: 99%